Sistem Informasi Pembayaran Rumah Kost Berbasis Website pada Elin Kost Garut - Elin Rosliani Rosliani; Cecep Fahmidin; Ikrimah Nurul (INTERNAL (Information System Journal), 2022)
Increasing technological developments can be utilized properly through various systems. However, some managers and prospective tenants of boarding house rental businesses will still have difficulty in having an integrated system. Many of them still make reservations for boarding houses directly at the location where the boarding house is located and there is limited information about the types and facilities of the rooms available. Elin Kost is one of the many boarding houses in Garut Regency that have not used the internet as a transaction medium in it. In making room reservation transactions, payments are made manually without using the internet, making it difficult for boarding house residents to view payment transaction history. The information system development method used is the waterfall method, namely needs analysis, system design, implementation, testing & testing, and uses SWOT analysis (Strength, Weakness, Opportunities, Threats) to find the source of the problem. Data collection methods are observation and literature study. The results showed that the application of a payment  information system was able to help increase Elin Kost sales because it facilitated the payment process. In addition, there is a need for development in the system so that it can provide more satisfying services to users.